A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes) - Carvalho, Marcelo R. De; Loboda, Thiago S.; Silva, João Paulo C. B. Da (Zootaxa, 2016)
A new subfamily (Styracurinae, subfam. nov.) and genus (Styracura, gen. nov.) are erected for Trygon schmardae Werner, 1904 (type species) and Dasyatis pacificus Beebe & Tee-Van, 1941, species placed in Himantura Müller & Henle, 1837 since 1953 but which differ significantly from it and all dasyatid genera in many morphological features. Recent molecular phylogenetic hypotheses based on the entire protein-coding mitochondrial genome have recovered Styracura as the sister group of the Neotropical freshwater stingrays (Potamotrygonidae), agreeing with previous morphological and molecular phylogenies. The Styracurinae, subfam. nov., is therefore placed in the Potamotrygonidae to reflect the current phylogenetic view. Morphological characters of phylogenetic relevance of the dermal denticles, ventral lateral-line canals, hyoid arch, cranial musculature, and pectoral and pelvic girdles are discussed and compared to other stingrays, in particular to dasyatids and potamotrygonins (now ranked as a subfamily). Inferred derived characters of Styracura and potamotrygonins require homoplasy (they are absent from Paratrygon and Heliotrygon), and ventral lateral-line canal patterns and morphology of the scapular process and pelvic girdle generally reveal an affinity to different dasyatid genera, but one most likely based on plesiomorphies or independent evolution; Styracura is considered more closely related to potamotrygonins.